Significance of Sampling Time on Thyroid-Stimulating Hormone, Free Thyroxine, and Free Triiodothyronine Levels: İmpact of sampling time on TSH, fT4, and fT3 parameters - Dağlar, Mahmut Mert; Orçun, Asuman (Journal of Medical Biochemistry, 2026)
Background: The timing of sample collection is crucial for analytes with a circadian rhythm. Although blood samples are usually obtained in the morning, they are often collected in the afternoon as well. Our study aims to evaluate the significance of the impact of sampling time on Thyroid-Stimulating Hormone (TSH), free thyroxine (fT4), and free triiodothyronine (fT3) parameters. Material and Methods: Serum TSH, fT4, and fT3 measurements from 216,278 patients who visited our institute’s outpatient clinics over a two-year period (2021–2023) were obtained from laboratory data. After exclusions 5,953 patient results collected from 8 am to 5 pm were grouped into 1-hour intervals. All measurements were conducted using the Cobas e801 (Roche Diagnostics, Penzberg, Germany), employing the electrochemiluminescence immunoassay method. Statistical significance was tested with the standard normal deviation test (Z-test) and clinical significance with bias % values obtained from biologic variation estimates on European Federation of Clinical Chemistry and Laboratory Medicine (EFLM) website. Results: Each TSH hourly group between 11 am and 5 pm showed statistically and clinically significant differences compared to the reference group. No statistically significant differences were observed for either fT4 or fT3. However, fT4 levels showed clinically significant difference at a single time point in males, while fT3 levels showed clinically significant differences between 3–5 pm in females and 2–5 pm in males. Conclusion: The analysis of our extensive data set indicates that the timing of blood sampling significantly affects TSH results. This may cause misinterpretation in clinical settings if standardization is not provided.